Pathogenicity and immunogenicity of fowl adenovirus of Malaysian isolate attenuated in chicken embryo liver cells in commercial broiler chickens - Mohamed Sohaimi, Norfitriah; Bejo, Mohd Hair; Omar, Abdul Rahman; Ideris, Aini; Mat Isa, Nurulfiza (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
The objective of this study was to determine pathogenicity and immunogenicity of Fowl adenovirus (FAdV) isolate of Malaysia (UPM1137) attenuated in chicken embryo liver (CEL) cells at passage 35 (CELP35) in commercial broiler chickens. The study demonstrated that the FAdV CELP35 isolate caused cytopathic effect (CPE) in the CEL cells with refractile, rounding and clumping of cells within 48 to 72 hours post-inoculation (pi). Four nucleotide (nt) bases changes were detected with 3 amino acids (aa) substitutions in L1 loop of hexon gene. In fiber gene, 4nt bases were substituted in knob region resulting 2aa changes. The CELP35 isolate belongs to FAdV group E serotype 8b and is safe and non-pathogenic in broiler chickens. High FAdV antibody response was detected at day 21pi as a result from the virus-induced immunity which is prominent via parenteral route. It was concluded that the FAdV isolate was attenuated, non-pathogenic and able to induce FAdV antibody response in chickens.